2021
DOI: 10.1177/1535370221992731
|View full text |Cite
|
Sign up to set email alerts
|

Biological evidence to define a vitamin A deficiency cutoff using total liver vitamin A reserves

Abstract: Vitamin A is a fat-soluble vitamin involved in essential functions including growth, immunity, reproduction, and vision. The vitamin A Dietary Reference Intakes (DRIs) for North Americans suggested that a minimally acceptable total liver vitamin A reserve (TLR) is 0.07 µmol/g, which is not explicitly expressed as a vitamin A deficiency cutoff. The Biomarkers of Nutrition for Development panel set the TLR cutoff for vitamin A deficiency at 0.1 µmol/g based on changes in biological response of several physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 67 publications
(149 reference statements)
0
7
0
1
Order By: Relevance
“…It has been pointed out that the effect of these factors on retinol levels does not necessarily reflect a good vit-A status, but merely that the body's retinol stores have been redistributed from the liver into circulation [ 37 ]. Meanwhile, an inadequate intake of vit-A for four months can lead to the depletion of retinol stores in the liver [ 38 ] and generate a deficiency in serum levels, as evidenced in adolescents in Brazil [ 39 ], China [ 40 ], the Philippines [ 41 ], Iran [ 42 ], and India [ 43 ]. Although it has been suggested that vit-A deficiency is manifested primarily as a subclinical disease in the Americas [ 44 ], it could generate deleterious effects on the health of adolescents through different pathways, such as those mentioned in the introduction [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been pointed out that the effect of these factors on retinol levels does not necessarily reflect a good vit-A status, but merely that the body's retinol stores have been redistributed from the liver into circulation [ 37 ]. Meanwhile, an inadequate intake of vit-A for four months can lead to the depletion of retinol stores in the liver [ 38 ] and generate a deficiency in serum levels, as evidenced in adolescents in Brazil [ 39 ], China [ 40 ], the Philippines [ 41 ], Iran [ 42 ], and India [ 43 ]. Although it has been suggested that vit-A deficiency is manifested primarily as a subclinical disease in the Americas [ 44 ], it could generate deleterious effects on the health of adolescents through different pathways, such as those mentioned in the introduction [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results show that model-predicted TBS for the young people with SCD-HbSS (428 μmol) was not significantly different from TBS predicted by RID at 3 d postdosing (389 μmol; Table 2 ); agreement between TBS predicted by population-based modeling and RID is not surprising [ 18 ], but it increases confidence in both approaches for estimating stores. Further, although mean plasma retinol concentration was lower in the subjects with SCD-HbSS than in healthy peers ( Table 1 ), mean TBS predicted by RID at 3 d postdosing was not significantly different in the 2 groups (389 and 406 μmol, respectively; Table 2 ), and mean estimated liver vitamin A concentrations were adequate in both groups (0.302 μmol/g and 0.277 μmol/g, respectively) compared with the currently used cutoff for adequate (>0.1 μmol/g) [ 46 ] and assuming that 80% of TBS is in the liver [ 40 ]. Also of interest, among the 11 subjects with SCD-HbSS for whom data were available on both day 3 and day 28 postdosing, RID predictions of TBS were not significantly different.…”
Section: Discussionmentioning
confidence: 99%
“…Liver concentrations of retinol of 0.07 μmol/g (as free retinol and retinyl esters) have been proposed as a criterium to define vitamin A adequacy and were used as a reference point to derive vitamin A requirements by different bodies (EFSA NDA Panel, 2015 ). More recently, the cut‐off for vitamin A deficiency has been revised to 0.1 μmol/g liver based on the fact that long‐term storage and biliary excretion do not occur below this liver retinol concentration (Tanumihardjo, 2021 ; Tanumihardjo et al., 2016 ).…”
Section: Assessmentmentioning
confidence: 99%